Vmesniki in pretvorniki: laboratorijske vaje - Kramberger, Iztok; Donaj, Gregor (2018)
Interfaces and Converters: Laboratory Work. Interfaces and converters for students of the professional higher education programme Electrical engineering (option electronics). The instructions contain 12 laboratory exercises dealing with converters, bridge circuits, amplifiers, and the use of RC circuits in conversions. The second part of the material deals with circuits for measuring non-electrical quantities: optical transducers, temperature sensor, humidity sensor, capacitor converter, Hall probe and liquid flow meter.
Keywords: electronics; laboratory work; interfaces; converters; sensors